Meaningful flesh : reflections on religion and nature for a queer planet - Bauman, Whitney (Punctum Books, 2017)
Religion is much queerer than we ever imagined. Nature is as well. These are the two basic insights that have led to this volume: the authors included here hope to queerly go where no thinkers have gone before. The combination of queer theory and religion has been happening for at least 25 years. People such as John Boswell began to examine the history of religious traditions with a queer eye, and soon after we had the indecent theology of Marcella Althaus Ried. At the same time, there have been many queer interrogations of "nature," perhaps most notably in the works of Joan Roughgarden, Ann Fausto-Sterling, Catriona Sandilands, and Timothy Morton. With the exception of Dan Spencer, one of the pioneers in this realm of thought, and Greta Gaard's development of queer ecofeminist thought, religion and nature, or religion and ecology, have largely ignored the realm of queer theory. In part, the blinders to queer theory on the part of eco-thinkers (religious or otherwise) are similar to the blinders eco-thinkers have when it comes to postmodern thought in general: namely, if there are no absolute foundations, how does one create an environmental ethic and a "nature" to save? These essays span different disciplines and themes, but are held together by the triple focus on religion, nature, and queer theory. Each of these essays offers a unique contribution to the intersection of religion, nature, and queer theory, and all of them challenge strict boundaries proposed in religious rhetoric and many discourses surrounding "nature."